Tari boran sebagai cerminan budaya dan kehidupan masyarakat Lamongan - Hafidh, Ena Nadhifah (Maliki Interdisciplinary Journal, 2025)
Tari Boran is a cultural heritage from Lamongan Regency that holds significant artistic, cultural, and philosophical values. Inspired by the lives of nasi boran vendors, this dance not only illustrates their daily activities but also reflects the spirit of perseverance and simplicity of Lamongan’s community. This article explores the history, philosophy, and role of Tari Boran in society, as well as the challenges faced in its preservation. Despite obstacles such as the declining interest of younger generations and limited financial support, various efforts have been made to sustain Tari Boran, including its integration into education and modifications in performances. Moreover, collaboration among the government, art communities, and the general public plays a crucial role in preserving this dance as part of Lamongan’s cultural identity. This article highlights the importance of preserving Tari Boran amidst modernization and cultural shifts while encouraging all stakeholders to contribute to safeguarding this invaluable local heritage.